Transforming Public Communication in Hajj Services: A Contextual Model of KBIHU-Based Information Strategies in North Sumatra - Indra, Farhan (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the effectiveness of public communication strategies implemented by Hajj and Umrah Guidance Groups (KBIHU) in North Sumatra within the framework of the Hajj implementation policy. While existing research on Hajj services largely focuses on logistics, health, and administrative systems, limited attention has been given to how the state communicates with pilgrims in a manner responsive to socio-cultural diversity and public trust challenges. This study addresses that gap by analysing how information services are designed, delivered, and received in a religious public service context. Using a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and document analysis involving Ministry of Religious Affairs officials, KBIHU managers, and Indonesian Hajj Brotherhood Association representatives. The findings reveal that public communication is dominated by one-way dissemination, lacks active involvement of local actors, and suffers from inconsistency in information delivery. These limitations hinder transparency, reduce trust in official channels, and increase reliance on informal sources. The study proposes a more participatory and adaptive communication framework that integrates two-way interaction, cultural sensitivity, and continuous engagement before, during, and after the Hajj season. The theoretical contribution lies in positioning this framework within the Situational Crisis Communication Theory (SCCT), extending its application to a socio-religious public service setting. This approach strengthens state legitimacy by reframing Hajj communication as administrative information delivery and as a trust-building process grounded in accountability, inclusion, and cultural context.